A Review on Green Chemistry and Its Applications - Yadav , Abhishek; Dubey, Adarsh (Asian Journal of Pharmaceutical Research and Development, 2024)
Green Chemistry is most investigated subject these days. It is also known as sustainable chemistry. Green Chemistry and sustainable chemistry are equals that helps to save and conserve resources. It decreases the effect of chemical products on human and atmospheric health. Green Chemistry gives 12 principles that reduce and prevent the utilization and manufacture of hazardous substance. These principles of green chemistry inform about the various issues related to production of chemical compound. Green Chemistry concept started approximately three decades ago. Green chemistry concept for the chemical synthesis and application launched in 1990. This review article purpose to study about Green chemistry and its application and how green chemistry connect to the phytochemistry. By establishing Green Aspiration Level (GAL) that is a quantifiable descriptor, process greenness becomes measurable. Green house gases and global warming are the problem that affected the human and environment health. Green chemistry is used in daily life mainly in medicines. Tree bark and Pine bark extracts are mostly used in anti-microbial, antioxidant and anticancer drugs. The matter that present in environment gives applicable things to the researchers and engineers for the changing and developing a sustainable culture. The word “Green chemistry” is given by the IUPAC which means: the invention, design and utilization of chemical product and process to reduce or to eliminate the use and production of unsafe substance.